The Concept of Moral Education in the Family Based on the Quran Surah Al-Isra' Verses 23-24 - Aditya Muhammad Anugrah (UNISBA Press, 2023)
Abstract. Moral education is an effort to develop morals so that humans have noble morals. The number of students fighting, drinking, gambling, insulting their parents, and even killing them shows a moral collapse among young people. As a result, methodical action to remedy this scenario is necessary, including enhancing the important role of parents and instructors in promoting student morale. In these circumstances, parents play an important role and are the most effective community to encourage good behavior in children. This research is a type of library research or library research. Library research is a type of research that collects data from various written sources, this study uses a qualitative research approach. The primary data in this study is a study of the text of the Qur'an, especially Surah iAl-Isra' verse i23-24. As well as various interpretations of Al such as the interpretation of Al Misbah, the interpretation of Al iAzhar, the interpretation of Jalalain and other interpretations. The main reason the author takes Surah Al-Isra' verses i23-24 is because there is an interest in the author of that letter, which according to the author still has values that have not been previously described. The data analysis techniques used by the authors in this study are content analysis techniques and literature review. The results of this study show that there are several essences contained in Al-Qur'an Surah Al-Isra' verses 23-24, namely: (1) Morals towards Allah Subhanahu Wata'ala, (2) Morals towards Family. The values of moral education in the Al-Qur'an surah Al-Isra' verses 23-24 are: (1) Tauhid Education and (2) Birrul Walidain Education (Morals Against Old People). Abstrak. Pendidikan akhlak imerupakan upaya untuk mengembangkan akhlak agar manusia berakhlak mulia. Banyaknya siswa yang berkelahi, minum minuman keras, berjudi, menghina orang tua, bahkan membunuh mereka menunjukkan keruntuhan moral di kalangan anak muda. Akibatnya, tindakan metodis untuk memulihkan skenario ini diperlukan, termasuk meningkatkan peran penting orang itua idan instruktur dalam mempromosikan moral siswa. Dalam keadaan ini, orang itua memainkan peran penting dan merupakan komunitas yang paling efektif iuntuk mendorong perilaku baik anak. Penelitian ini merupakan jenis penelitian kepustakaan atau library research. Penelitian kepustakaan merupakan jenis penelitian yang mengumpulkan data-data idari berbagai sumber tertulis, penelitian ini menggunakan pendekatan penelitian kualitatif. Data primer dalam penelitian ini adalah kajian teks Al-Qur’an, khususnys Surat iAl-Isra’ iayat i23-24. Serta berbagai tafsir Al seperti tafsir Al Misbah, tafsir Al iAzhar, tafsir Jalalain dan tafsir-tafsir lainnya. Alasan utama penulis mengambil Surat Al-Isra’ iayat i23-24 karena ada ketertarikan penulis terhadap surat itu iyang imenurut penulis masih ada inilai nilai iyang belum terdeskripsikan sebelumnya. Adapun teknik analisis data yang idigunakan oleh penulis dalam penelitian ini yaitu teknik analisis konten (Content iAnalysis) dan pengkajian literatur. Hasil dari penelitian ini menunjukan bahwa terdapat beberapa esensi yang terkandung dalam Al-Qur’an Surat Al-Isra’ ayat 23-24 yaitu: (1) Akhlak iterhadap Allah Subhanahu Wata’ala, (2) Akhlak terhadap Keluarga. Nilai-nilai pendidikan akhlak dalam Al-Qur’an surat Al-Isra’ ayat 23-24 yaitu: (1) Pendidikan Tauhid dan (2) Pendidikan Birrul Walidain (Akhlak Terhadap Orang iTua).